Pure solid wood heating floor based on surface anti-cracking enhanced modification process

By using a combination of high elastic primer layer and fiberglass cloth layer on wooden floors and combining anti-wear topcoat layer, the fabric material problems caused by floor size changes are solved, and the structural stability and service life of the floor are improved. Improves fabric effect and anti-photoaging performance.

CN222271514UActive Publication Date: 2024-12-31JIUSHENG WOOD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420849008.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2024-12-31
Estimated Expiration
2034-04-23

AI Technical Summary

Technical Problem

When existing wooden floors are affected by external temperature and humidity, the dimension changes cause the fabric material to be unable to deform with the floor, causing wrinkles, layering and paint film to fall off. Low-hardness materials are used to reduce the hardness of the floor and have a short service life.

Method used

Adopt a modification process based on surface crack-proof reinforcement, including a high elastic primer layer, a glass fiber cloth layer and an anti-wear topcoat layer. The high elastic primer layer is used to buffer the deformation of the substrate, and the glass fiber cloth layer is adhered by a photocuring resin. On the high elastic primer layer, combining adhesion, high-definition hardness and wear-resistant primer layer, improve the structural stability and impact resistance of the floor.

Benefits of technology

It effectively avoids wrinkling and layering of glass fiber cloth, improves the film strength, structural stability and service life of the floor, and improves the fabric effect and photoaging resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222271514U_ABST
    Figure CN222271514U_ABST
Patent Text Reader

Abstract

The utility model discloses a pure solid wood heating floor based on a surface anti-cracking enhanced modification process, which comprises a base plate (1), the surface of the base plate (1) is sequentially provided with a high-elasticity primer layer (2), a glass fabric layer (3) and an anti-wear finish paint layer (4) from bottom to top, and the anti-wear finish paint layer (4) fluctuates along with the surface of the glass fabric layer (3) after being coated. The high-elasticity primer layer (2) is used for buffering the glass fabric layer (3) through local deformation when the base plate (1) shrinks or rises, and the glass fabric layer (3) is prevented from wrinkling or layering along with deformation of the base plate (1). According to the utility model, the cloth cover effect of the floor surface can be improved, and the paint film strength, structural stability and service life of the floor are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to a floor heating floor, in particular to a pure solid wood floor heating floor based on a surface anti-crack enhancement modification process. Background Art

[0002] As user aesthetics and needs change, the market demand for fabric floor products with special surface decoration effects and touch is increasing. However, since wooden floors will shrink and swell due to external environmental factors such as temperature and humidity, if manufacturers directly adhere high-strength fabric materials to the floor surface to achieve the fabric effect, the fabric materials will not be able to deform along with the wooden floor, and this difference in size change will cause wrinkling, stratification, and even paint film peeling on the floor surface, causing permanent damage to the fabric effect. If a material with higher toughness and lower hardness is used as the fabric layer to reduce the difference in size change, it is easy to cause a serious decrease in the hardness and strength of the floor, and the service life of the floor is greatly reduced, which cannot meet the daily use needs of customers. Under the above restrictions, it is difficult for current manufacturers to achieve the fabric effect of wooden floors by directly laying fabric materials on the floor surface.

[0003] In this regard, manufacturers currently generally use surface grooving to achieve a cloth effect. Specifically, as shown in Patent 201811484596.1, by opening a number of regular horizontal and vertical grooves on the floor surface, the floor can be close to the texture and touch of cloth after grooving. However, this method is not only complex in process and low in production efficiency, but also the cloth structure formed by grooving is difficult to fully achieve the visual effect and touch of real cloth, thus reducing the user experience of cloth flooring.

[0004] Therefore, the existing processing method for fabric flooring has the problems of complex production process, low production efficiency and poor fabric effect. Utility Model Content

[0005] The purpose of the utility model is to provide a pure solid wood floor heating floor based on a surface crack prevention and enhancement modification process, which can improve the cloth effect of the floor surface and ensure the paint film strength, structural stability and service life of the floor.

[0006] The technical solution of the utility model: a pure solid wood floor heating floor based on a surface anti-cracking enhanced modification process, comprising a substrate, wherein a high-elastic primer layer, a glass fiber cloth layer and an anti-wear topcoat layer are sequentially arranged on the surface of the substrate from bottom to top, wherein the anti-wear topcoat layer forms undulations along with the surface of the glass fiber cloth layer after coating, and the high-elastic primer layer is used to buffer the glass fiber cloth layer through local deformation when the substrate shrinks or expands, thereby avoiding wrinkling or delamination of the glass fiber cloth layer caused by deformation of the substrate.

[0007] In the above-mentioned pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process, the high elastic primer layer is formed by sequentially coating two layers of high elastic primer monolayers, and the coating amount of each layer of high elastic primer monolayer is 10-30g / m 2 .

[0008] In the aforementioned pure solid wood floor heating floor based on surface crack prevention and enhancement modification process, the surface of the glass fiber cloth layer is provided with a light-curing resin impregnation layer, and the light-curing resin impregnation layer is used to adhere the glass fiber cloth layer to the high-elastic primer layer.

[0009] In the aforementioned pure solid wood floor heating floor based on the surface anti-cracking enhanced modification process, an adhesion primer layer and a high-definition hardness primer layer are sequentially coated between the substrate and the high-elasticity primer layer from the inside to the outside.

[0010] In the above-mentioned pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process, the coating amount of the adhesion primer layer is 10 to 30 g / m 2 The coating amount of the high-definition hardness primer layer is 20 to 30 g / m 2 .

[0011] In the aforementioned pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process, a wear-resistant primer layer is provided between the glass fiber cloth layer and the wear-resistant topcoat layer.

[0012] In the above-mentioned pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process, the coating amount of the wear-resistant primer layer is 10 to 30 g / m 2 The coating amount of the anti-wear topcoat layer is 5 to 10 g / m 2 .

[0013] In the aforementioned pure solid wood floor heating floor based on the surface anti-cracking and enhanced modification process, the glass fiber cloth layer is paved with medium-alkali glass fiber cloth, and the thickness of the glass fiber cloth layer is 0.08-0.5 mm.

[0014] Compared with the prior art, the utility model has the following characteristics:

[0015] (1) The utility model provides a high elastic primer layer on the inner side of the glass fiber cloth layer, so that when the substrate shrinks or expands, the high elastic primer layer can be used for buffering, that is, the inner side of the high elastic primer layer deforms together with the floor, and the outer layer of the high elastic primer layer is restricted by the glass fiber cloth layer to maintain its original state, thereby utilizing the local deformation of the high elastic primer layer itself to adapt to the structural changes on both sides of the inner and outer sides, thereby preventing the substrate from transmitting the lateral deformation to the glass fiber cloth layer and causing the glass fiber cloth layer to wrinkle or tear, thereby improving the structural stability and service life of the floor;

[0016] (2) After the medium-alkali glass fiber cloth is laid on the floor surface, the alkaline metal compounds in the glass fiber cloth can also absorb part of the ultraviolet rays in the external light, thereby effectively improving the anti-light aging performance of the floor; by adhering the glass fiber cloth layer to the high-elastic primer layer after being soaked in light-curing resin, on the one hand, the connection stability between the glass fiber cloth layer and the high-elastic primer layer can be ensured, and the glass fiber cloth layer can be prevented from falling off on the high-elastic primer layer; on the other hand, after being cured, the light-curing resin can cooperate with the glass fiber cloth layer to form a high-hardness structure, that is, effectively improving the deformation resistance of the glass fiber cloth layer, so that the glass fiber cloth layer can maintain its own state unchanged when subjected to the lateral deformation force from the high-elastic primer layer, thereby ensuring the local deformation effect of the high-elastic primer layer;

[0017] (3) By setting up the adhesion primer layer, the high-definition hardness primer layer, the wear-resistant primer layer and the wear-resistant topcoat layer, the impact resistance, wear resistance, light aging resistance, flame retardancy and the bonding performance between the paint film and the wood part of the floor surface can be improved; and under the above combination, the wear resistance of the paint film surface of the utility model reaches 0.063g / 100r, the impact resistance reaches 11.6mm, and the cigarette burn resistance level reaches level 2, which ensures the physical and chemical properties of the floor after laying the glass fiber cloth layer;

[0018] With the above-mentioned coordination, the present invention can adhere the fiberglass cloth to the floor surface to achieve a cloth effect, which effectively improves the authenticity of the cloth effect compared to the existing cloth floor formed by grooves, makes it have a good cloth touch and visual effect, and ensures the paint film strength, structural stability and service life of the floor. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the structure of the utility model in a normal state;

[0020] Figure 2 It is a schematic diagram of the structure of the utility model when the substrate is in a dry and shrunk state;

[0021] Figure 3 is a surface state diagram of comparative example 1 after testing in experimental example 1;

[0022] Figure 4 is a surface state diagram of comparative example 2 in experimental example 1 after testing;

[0023] Figure 5 is a surface state diagram of comparative example 1 in experimental example 3 after testing;

[0024] Figure 6 is a surface state diagram of comparative example 2 in experimental example 3 after testing;

[0025] Figure 7 is a surface state diagram of comparative example 3 after testing in experimental example 3;

[0026] Figure 8 is a surface state diagram of comparative example 1 in experimental example 4 after testing;

[0027] Fig. 9 This is a surface state diagram of comparative example 2 in experimental example 4 after testing.

[0028] The markings in the attached drawings are: 1-substrate, 2-high elastic primer layer, 3-fiberglass cloth layer, 4-wear-resistant topcoat layer, 5-adhesion primer layer, 6-high hardness primer layer, 7-wear-resistant primer layer, 8-light-curing resin impregnation layer. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.

[0030] Embodiment. A pure solid wood floor heating floor based on a surface anti-cracking and enhanced modification process is composed of Figure 1 As shown, it includes a substrate 1, and a high-elastic primer layer 2, a glass fiber cloth layer 3 and an anti-wear topcoat layer 4 are sequentially arranged on the surface of the substrate 1 from bottom to top. The glass fiber cloth layer 3 is a medium-alkali glass fiber cloth with a conventional grid structure. The thickness of the glass fiber cloth layer 3 is 0.1 mm. A number of fine meshes are evenly distributed on the glass fiber cloth layer 3. After coating, the anti-wear topcoat layer 4 forms a grid-like undulation along the surface of the glass fiber cloth layer 3, that is, a cloth surface effect is formed; the high-elastic primer layer 2 is used to buffer the glass fiber cloth layer 3 through local deformation when the substrate 1 shrinks or expands, so as to avoid wrinkling or delamination of the glass fiber cloth layer 3 caused by deformation of the substrate 1.

[0031] The flexibility of the paint film of the high elastic primer layer 2 needs to be controlled to be no more than 1 mm in diameter according to the measurement standard of GB / T1731-2020. Specifically, the 128804511 type high elastic primer of Jiangsu Haitian Technology Co., Ltd. can be used. The high elastic primer layer 2 is formed by coating two layers of high elastic primer monolayers in sequence, and the coating amount of each layer of high elastic primer monolayer is 20 g / m 2 , each coat was cured individually and polished using a 400 grit sanding belt.

[0032] The surface of the glass fiber cloth layer 3 is provided with a light-curing resin impregnation layer 8, and the material of the light-curing resin impregnation layer 8 can be selected from K-3022 type film-forming light-curing resin glue, and the light-curing resin impregnation layer 8 is used to adhere the glass fiber cloth layer 3 to the high elastic primer layer 2; when processing the light-curing resin impregnation layer 8, firstly, the surface of the high elastic primer layer 2 is coated with 30g / m 2A layer of film-forming photocurable resin is applied with a coating amount of, and then the glass fiber cloth fully impregnated with the film-forming photocurable resin is applied to the surface of the high-elastic primer layer 2, and then the glass fiber cloth is flattened with a rubber scraper to make the glass fiber cloth and the high-elastic primer layer 2 completely bonded and remove excess film-forming photocurable resin on the surface of the glass fiber cloth. Finally, the film-forming photocurable resin on the surface of the glass fiber cloth is completely cured to form a photocurable resin impregnation layer 8; after curing, the glass fiber cloth forms a grid structure on the surface of the high-elastic primer and adheres to the surface of the glass fiber cloth and the bottom of the mesh, thereby forming an integrated structure and providing a bonding interface for the upper paint layer, thereby preventing the upper paint layer from directly contacting the high-elastic primer and the glass fiber cloth during coating.

[0033] An adhesion primer layer 5 and a high-definition hardness primer layer 6 are sequentially coated between the substrate 1 and the high-elasticity primer layer 2 from inside to outside. The high-definition hardness primer layer 6 can be formed by coating with FG-129200 high-definition hardness paint produced by Jiangsu Haitian Technology Co., Ltd.

[0034] The coating amount of the adhesion primer layer 5 is 20 g / m 2 The adhesion primer layer 5 is fully cured after coating and then polished with a 400-mesh sand belt; the coating amount of the high-definition hardness primer layer 6 is 25g / m 2 , HD hardness primer layer 6 was fully cured after application and polished using a 400 grit sanding belt.

[0035] A wear-resistant primer layer 7 is provided between the glass fiber cloth layer 3 and the wear-resistant topcoat layer 4 .

[0036] The coating amount of the wear-resistant primer layer 7 is 20 g / m 2 The wear-resistant primer layer 7 is completely cured after coating and polished with a scouring pad or Dupont silk; the coating amount of the wear-resistant topcoat layer 4 is 10g / m 2 The anti-wear topcoat layer 4 is completely cured after coating and is polished with a scouring pad or Dupont silk.

[0037] Working principle of the utility model: The utility model sets a high elastic primer layer 2 between the substrate 1 and the glass fiber cloth layer 3, so that the inner and outer sides of the high elastic primer layer 2 change with the size of the substrate 1 and the glass fiber cloth layer 3 respectively; when the substrate 1 shrinks or expands, the inner side of the high elastic primer layer 2 can shrink or expand together with the substrate 1, and the outer side of the high elastic primer layer 2 can keep its size unchanged under the restriction of the glass fiber cloth layer 3, thereby playing a buffering effect, avoiding the glass fiber cloth layer 3 from being directly affected by the substrate 1 and wrinkling or tearing, and improving the structural stability of the glass fiber cloth layer 3 after adhesion. By setting the high hardness primer layer 6, the wear-resistant primer layer 7 and the wear-resistant topcoat layer 4, the impact resistance and wear resistance of the floor surface can be improved. Thus, the performance requirements of the floor are met.

[0038] Experimental Example 1: In this experiment, two wooden boards of the same size and material are used as substrates, and the two substrates are processed to obtain comparative examples 1 and 2, respectively. Comparative example 1 is based on the pure solid wood floor heating floor in the embodiment and removes the high elastic primer, glass fiber cloth and light-cured resin on the surface of the substrate; comparative example 2 is the pure solid wood floor heating floor in the embodiment. Then, the impact resistance of the two groups of comparative examples was tested using the test standard in GB / T18102-2020 "Impregnated Paper Laminated Wood Floor" (steel ball 42.8mm diameter, 1.75m height).

[0039] The test results are as follows Figure 3 and Figure 4 As shown, Figure 3 This is the surface status diagram of comparative example 1 after the test. The thickness of the mark on comparative example 1 after the impact of the steel ball is 14.4 mm, and a large number of obvious cracks appear on the paint film on the floor surface, indicating that the paint film conventionally set on the floor surface will have obvious crack problems after being impacted by a heavy object. Figure 4 This is the surface status diagram of Example 2 after the test. The thickness of the mark on Example 2 after the impact of the steel ball is 11.6 mm, and there are no obvious cracks on the surface of the floor, indicating that the glass fiber cloth can reinforce the paint film on the surface of the floor after paving, and alleviate the deformation and rupture of the paint film after the impact.

[0040] Experimental Example 2: This experiment uses the technical requirements in GB / T15036.1-2018 to test the surface wear resistance of the paint film on the floor in the embodiment. The test shows that the paint wear amount of this embodiment is 0.063g / 100r, which meets the wear resistance requirements of high-quality solid wood flooring.

[0041] Experimental Example 3: This experiment uses three wooden boards of the same size and material as substrates, and processes the three substrates to obtain Comparative Example 1, Comparative Example 2 and Comparative Example 3 respectively; Comparative Example 1 is based on the pure solid wood floor heating floor in the embodiment and removes the high elastic primer on the surface of the floor; Comparative Example 2 is based on the pure solid wood floor heating floor in the embodiment and only applies a single layer of high elastic primer on the surface of the high hardness primer, and the coating amount is 20g / m 2 ; Comparative Example 3 is the pure solid wood floor heating floor in the embodiment.

[0042] Then the three groups of comparative examples were placed in an oven at 60°C to simulate the geothermal environment, and the glass fiber cloth morphology on the surface of the three groups of comparative examples was observed after 24 hours. Figure 5-7 As shown, Figure 5 This is a surface state diagram of comparative example 1. In the diagram, the fiberglass cloth on the floor surface forms dense and continuous wrinkles after the test, indicating that the existing method of directly laying the fiberglass cloth on the floor surface will cause the fiberglass cloth to wrinkle or delaminate as the substrate shrinks and expands. Figure 6This is the surface state diagram of comparative example 2. In the figure, the glass fiber cloth on the floor surface has several white dots or lines after the test, indicating that the glass fiber cloth also has local wrinkling or delamination in this area and cannot completely overcome the impact caused by the shrinkage and expansion of the substrate. Figure 7 This is a surface state diagram of comparative example 3. It can be seen from the figure that the present invention can effectively avoid wrinkling or delamination problems on the surface of the glass fiber cloth by setting a high-elastic primer, thereby achieving the stability and service life of the glass fiber cloth after paving.

[0043] Experimental Example 4: Using Comparative Example 1 and Comparative Example 2 in Experimental Example 1 as samples, the two groups of samples were subjected to 12 hours of xenon lamp aging treatment, and the lower half of the floor was shielded with opaque material during the treatment. Figure 8-9 As shown, Figure 8 This is the surface status diagram of comparative example 1 after the test. From the picture, it can be seen that the upper and lower parts of comparative example 1 after the light aging test form an obvious contrast between light and dark, indicating that the surface of a conventional floor without medium-alkali glass fiber cloth will have a discoloration problem after long-term light exposure. Fig. 9 This is a surface state diagram of comparative example 2 after the test. It can be seen from the picture that the upper and lower parts of comparative example 2 after the light aging test are basically the same in color, and there is no obvious difference in light and dark, indicating that the present invention can improve the anti-light aging performance of the floor by paving the medium-alkali glass fiber cloth on the surface of the floor.

Claims

1. Pure solid wood floor heating floor based on surface anti-cracking and enhanced modification process, characterized by: The invention comprises a substrate (1), wherein a high elastic primer layer (2), a glass fiber cloth layer (3) and an anti-wear topcoat layer (4) are sequentially arranged on the surface of the substrate (1) from bottom to top, wherein the anti-wear topcoat layer (4) forms undulations along with the surface of the glass fiber cloth layer (3) after coating, and the high elastic primer layer (2) is used to cushion the glass fiber cloth layer (3) through local deformation when the substrate (1) shrinks or expands, thereby preventing the glass fiber cloth layer (3) from wrinkling or delamination due to deformation of the substrate (1).

2. The pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process according to claim 1 is characterized in that: The high elastic primer layer (2) is formed by sequentially coating two layers of high elastic primer monolayers, and the coating amount of each layer of high elastic primer monolayer is 10-30 g / m 2 .

3. The pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process according to claim 1 is characterized in that: The surface of the glass fiber cloth layer (3) is provided with a light-curing resin impregnation layer (8), and the light-curing resin impregnation layer (8) is used to adhere the glass fiber cloth layer (3) to the high-elastic primer layer (2).

4. The pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process according to claim 1 is characterized in that: An adhesion primer layer (5) and a high-hardness primer layer (6) are sequentially coated between the substrate (1) and the high-elasticity primer layer (2) from the inside to the outside.

5. The pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process according to claim 4 is characterized in that: The coating amount of the adhesion primer layer (5) is 10 to 30 g / m 2 The coating amount of the high-definition hardness primer layer (6) is 20 to 30 g / m 2 .

6. The pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process according to claim 1 is characterized in that: A wear-resistant primer layer (7) is provided between the glass fiber cloth layer (3) and the wear-resistant topcoat layer (4).

7. The pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process according to claim 6 is characterized by: The coating amount of the wear-resistant primer layer (7) is 10 to 30 g / m2, and the coating amount of the wear-resistant topcoat layer (4) is 5 to 10 g / m2. 2 .

8. The pure solid wood floor heating floor based on the surface crack prevention and enhancement modification process according to claim 1 is characterized by: The glass fiber cloth layer (3) is formed by paving medium-alkali glass fiber cloth, and the thickness of the glass fiber cloth layer (3) is 0.08-0.5 mm.